Tiger woman on Wall Street : winning business strategies from Shanghai to New York and back - Li, Junheng (New York : McGraw-Hill Education, 2014)
'Powerful methods for global investing from a dual expert on Chinese and U.S. markets Tiger Woman on Wall Street is the remarkable story of how one woman has risen to the top of the traditionally male-dominated world of finance. Raised by'tiger parents' in China in the 1980s, when the Chinese economy was just starting to boom, Junh Li came to the United States to attend college and climbed her way up to the top with a relentless personal drive and a remarkable talent for investing and finance.Tiger Woman on Wall Street is both an autobiographical tell-all and a critical review of Chinese and American comparative cultures and economies. It gives international investors both the insight and the hard advice they need to navigate the increasing complexities of the global economy.Junheng Li runs the independent equity research firm, JL Warren Capital LLC, to advise institutional asset managers on investing in small- to mid-capitalization companies both in the U.S. and China. She was previously senior equity analyst at Aurarian Capital Management'--
Includes bibliographical references and index.
Keywords: Li, Junheng; Capitalists and financiers -- United States -- Biography; Capitalists and financiers -- China -- Biography; Investments; Success in business